Devotional Islam in contemporary South Asia: shrines, journeys and wanderers - Boivin, Michel; Delage, Rémy (Routledge contemporary South Asia series, 2016)
Authority, Shrines and Spaces: Scrutinizing devotional Islam from South Asia / Michel Boivin -- Vagrancy and pilgrimage according to the Sufi Qalandari path: the illusions of anti-structure / Alexandre Papas -- Qalandars and Ahl-e Haqq / Mojan Membrado -- Woman [Un] like Woman: the question of spiritual authority among female fakirs of Sehwan Sharif / Omar Kasmani -- Negotiating religious authority at a shrine Inhabited by a living saint "the dargah of "Zinda" Shah Madar / Ute Falasc -- How discourses construct figures of holiness: the example of the Indo-Muslim Martyr Ghazi Miyan (Uttar Pradesh, North India) / Delphine Ortis -- Meditative practice, aesthetics and entertainment music in an Indian Sufi shrine / Mikko Viitamäki -- Evolution of the Chishti Shrine and the Chishtis in Pakpattan (Pakistan) / Muhammad Mubeen --The mother and the other: tourism and pilgrimage at the shrine of Higlaj Devi/Bibi Nani in Baluchistan / Jürgen Schaflechner -- Sacred journeys, worship and reverence: the Sufi legitimation of the ziyarat in Hyderabad / Mauro Valdinoci -- An ambiguous and contentious politicization of Sufi shrines and pilgrimages in Pakistan / Alix Philippon